A Novel Method for Extracting Time Series Information of Deformation Area of a Single Landslide Based on Improved U-Net Neural Network - Dai, Bibo; Wang, Yunmin; Ye, Chunyang; Li, Qihang; Yuan, Canming; Lu, Song; Li, Yuyang (Frontiers in Earth Science, 2021)
This paper proposed an improved U-Net fully convolutional neural network to automatically extract a single landslide deformation information under time series based on the physical model experiments. This method extracts time series information for three different landslide deformation ranges. Compared to U-Net and mainstream superpixel method, evaluation indicators of DSC, VOE and RVD verify the high recognition accuracy and strong robustness of our method.